CLASSIFICATION OF ORAL POTENTIAL MALIGNANT DISORDERS (OPMDS) AND NORMAL REGION OF ORAL CAVITY USING VELSCOPE IMAGES - ,, MUHAMMAD AWAIS (2016)
Oral Potential Malignant Disorders (OPMDs) and cancerous cells inside the mouth cavity is an important health issue throughout the world. Government and healthcare practitioners put high priority to control and limit the mortality due to this fatal disease. Traditionally, the main method for the diagnosis of oral disorders is the biopsy. However, it is considered as an invasive and painful process for the patients. Currently, along with conventional oral examinations (COE), there are a variety of commercial diagnostic methods and devices available such as toluidine blue, light based detection system (ViziLite® plus) and narrow-emission tissue fluorescence (VELscope® and Identafi®). Although these screening devices help the doctors in finding the abnormal areas inside the oral cavities, the use of these devices depends on human observation to differentiate between a cancerous lesion and normal region.